Hubungan efikasi diri dengan resiliensi warga perumahan aspol bangkingan selama masa pandemi COVID -19 (SUKMA : Jurnal Penelitian Psikologi, 2022)
The number of people experiencing mental health problems during this pandemi is understandable considering that Covid - 19 is a new source of stress for the world community today, one of those affected is the residents of the Bangkingan Aspol housing complex. The problems faced and the difficulties experienced by these residents require residents to have a psychological aspect that can improve or maintain their psychological condition in dealing with the current situation and conditions. The data collection technique used was purposive sampling (judgmental sampling) where there was a 5% error tolerance and based on the sampling of 150 people, the number of subjects in this study were 105 respondents. Self-efficacy and resilience scales in the form of a questionnaire were filled out for each topic and Spearmans Rho correlation analysis was carried out which showed a correlation coefficient = 0.410 (quite strong correlation) and p = 0.000 (p <0.01) based on the results of hypothesis testing showed that the hypothesis the researchers formulated accordingly, namely that there is a positive relationship between self-efficacy and resilience. This means that the self-efficacy of residents affects the resilience of each individual, so that residents who have positive self-efficacy tend to be more resilient. On the other hand, if the self-efficacy is lower, each citizen will have lower resilience. Keywords: Self-Efficacy, Resilience